Probiotics in intestinal modulation as an adjuvant in the treatment of signs and symptoms of depression (Research, Society and Development, 2021)
Objective: This study aimed to investigate whether probiotics improved symptoms of depression and anxiety as assessed by different psychometric scales. Methodology: The present study is an integrative bibliographic review, carried out through a literature survey bibliographic research in PubMed combining the terms "Probiotics", "Intestinal Modulation" and "Depression" to identify clinical trial studies in humans who investigated the relationship between depressive, anxious aspects and the microbiota. Results: Data were extracted from 12 studies of clinical trials (922 humans), randomized, controlled, doubleblind.  In the assessed context, probiotics reduced scores on different psychometric scales, reducing anxiety-like and depressive behavior.  Analyzes of analyzes at the level of probiotic species, identified subspecies of the genus Lactobacillus and Bifidobacterium the capacity for anxiolytic activity.  ⩾60% improvements in evaluation scales were demonstrated with supplementation of probiotics and even improvements in quality of life in individuals with inflammatory bowel diseases. Conclusion: The microbiota was raised to a potential target for the treatment of psychiatric and antidepressant disorders.  Depression is a challenge for global health, as it requires multidisciplinary interventions since this disease is characterized as a cerebral metabolic disorder and probiotics would play an essential role on the individual's health and disease status.